Influence of microbial colonization of the endometry on its function and development of hyperproliferative conditions - Khaskhachikh, Dmytro; Potapov, Valentin (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2023)
Abstract. The article provides an overview of literary sources that describe  research on the microbiome of the endometrium in women of reproductive age. Thus, in many works, data is given indicating that the uterine cavity is not sterile. Various microorganisms can be found on the surface of the endometrium. So far, there is not enough research on microorganisms that can be considered a normal microbiome of the endometrium and its influence on the function and development of hyperproliferative processes of the endometrium in women. Many studies have proven the undoubted role of the uterine microbiome in the development of endometrial hyperplasia and other proliferative diseases. The cited studies indicate that 60 % of examined women with signs of microbial colonization caused by an infection of viral, bacterial, or fungal origin developed endometrial dysfunction, which led to the development of hyperproliferative processes. The study of the microbiocenosis of the uterine cavity in patients of reproductive age with various types of endometrial pathology indicates the role of certain pathogenic microflora in their occurrence. In all cases of atypical proliferation of the endometrium, an increase in the number of anaerobes up to 30 % was found among all isolated microorganisms, in particular, anaerobic bacteria of the genus Bacteroides spp. Representatives of the Enterobacteriaceae family (E. coli) and Gram-positive cocci (staphylococci and streptococci) prevailed among the aerobic flora. The largest spectrum of isolated microorganisms was found in patients with endometrial polyps. Studies of the immune system of the endometrium, which is formed to a greater extent due to the microbiome and directly participates in the cyclic changes of the endometrium, which are necessary for its physiological function during reproduction, are also presented. The immune system of the endometrium participates in the cyclic changes of the endometrium necessary for its physiological function in the process of reproduction. A proven factor is cells of the immune system and proper remodeling of spiral arteries, NK (neutrophil killer), T-lymphocytes and antigen-presenting cells (APC – antigen-presenting cell). A very important factor in the interaction between the gut microbiome and the immune system is the gut mucosa, and from this it can be inferred that similar connections may exist for the endometrium and its microbiome. Further studies of the state of the microbiome of the uterine cavity will allow adding information about its participation in functional processes and the pathogenesis of the development of hyperproliferative endometrial conditions.